2022
DOI: 10.3390/coatings12070984
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of the Interfacial Damage in EB-PVD Thermal Barrier Coating

Abstract: Considering the influence of non-equibiaxial stress state and initial residual strain on the compressive buckling of the ceramic layer, a quantitative characterization method of the damage generated at the interface between the top coat and bond coat in thermal barrier coating based on uniaxial compression was developed. It was verified by the axial compression tests of the single crystal specimens with EB-PVD thermal barrier coating after undergoing various isothermal oxidation times and thermal cycles. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Existing studies have shown that the thermal mismatch stress inside the TC layer and the TGO layer is the main reason for the peeling and failure of the TBC system [ 55 ]. In addition, volume expansion induced by the phase transition of the TC layer will accelerate the initiation and propagation of cracks [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that the thermal mismatch stress inside the TC layer and the TGO layer is the main reason for the peeling and failure of the TBC system [ 55 ]. In addition, volume expansion induced by the phase transition of the TC layer will accelerate the initiation and propagation of cracks [ 56 ].…”
Section: Introductionmentioning
confidence: 99%